Pengaruh Pendapatan Asli Daerah Terhadap Belanja Modal Pada Pemerintah Kota Sukabumi - Desi Rahayu Agustian (Jurnal Akuntansi UMMI, 2020)
This study aims to determine how much influence the local revenue to capital expenditure in the local government of Sukabumi. Independent variables used in this research is the local revenue, and the dependent variable used is capital expenditure. The sample used in this study is the realization of the budget report for 36 months of 2012-2014. The method used in this research is descriptive method with associative method. Data analysis techniques used in this study is a simple linear regression analysis. Hypothesis testing is done by using the t test and the coefficient of determination. Processing data using statistical product and service solutions. (SPSS)23. Based on the results of the analysis showed that the value ajusted R2 is equal to 0.698, which means that the local revenue effect on capital spending by 48.7%, while 51.3% are influenced by other factors not mentioned in the study.